Determining the influence of Itaipu Lake on thermal conditions for soybean development in adjacent lands - C. Wagner-Riddle; S. S. Werner; P. Caramori; W. S. Ricce; P. Nitsche; P. von Bertoldi; E. F. de Souza (International Journal of Biometeorology, 2015)
Previous numerical simulations have suggested that the area adjacent to Itaipu Lake in Southern Brazil is significantly affecting the local thermal regime through development of a lake breeze. This has led to concerns that soybean growth and development, and consequently yield, has been affected by the creation of the artificial lake in this important agricultural region, but a systematic climatological study of the thermal effects of Itaipu Lake has not been conducted. The objectives of this study were to assess the spatial pattern of minimum and maximum air temperatures in a 10-km-wide area adjacent to Itaipu Lake as affected by distance from the water. Measurements were conducted over 3 years in seven transects along the shore of Itaipu Lake, with five weather stations placed in each transect. Phenological observations in soybean fields surrounding the weather stations were also conducted. Generalized additive models for location, scale, and shape (GAMLSS) analysis indicated no difference in the temperature time series as distance from water increased. Semivariograms showed that the random components in the air temperature were predominant and that there was no spatial structure to the signal. Wind direction measured over the three growing seasons demonstrated that, on average, the development of a lake breeze is limited to a few locations and a few hours of the day, supporting the temporal and spatial analysis. Phenological observations did not show differences in the timing of critical soybean stages. We suggest that the concerns that soybean development is potentially affected by the presence of Itaipu Lake are not supported by the thermal environment observed.